Evaluating open source software using the selection criteria and analytical hierarchy process. - Jusoh, Yusmadi Yah; Chamili, Khadijah; Yahaya, Jamaiah; Che Pa, Noraini (American-Eurasian Network for Scientific Information, 2013)
There are many potential and good open source software (OSS) products available in the market with free license. However, with various choices, the adoption rate is still low among OSS potential users because there is not an agreed acceptable set of criteria to evaluate and decide varieties of OSS products, with little documentation and user manuals, and immature products. Therefore, the users need to consider on how to improve decision making on selecting the most suitable OSS products. In this paper, the background research on the proposed OSS adoption and criteria of selection are discussed and explored which then moves to the implementation of the My Open Source Software Toolkit (MyOSST) v1.0. The analytical hierarchy process (AHP) was applied for selecting the most suitable OSS products and assisting the potential user for deciding the OSS products based on their preferred selection criteria. The toolkit will support the OSS adoption process with proposed criteria selection and pair wise comparison. The toolkit was tested and validated by IT professionals capable to assist the decision making on selecting an appropriate OSS product.